1993
DOI: 10.1007/bf00401152
|View full text |Cite
|
Sign up to set email alerts
|

Human monoclonal islet specific autoantibodies share features of islet cell and 64 kDa antibodies

Abstract: Summary.The first human monoclonal islet cell antibodies of the IgG class (MICA 1-6) obtained from an individual with Type 1 (insulin-dependent) diabetes mellitus were cytoplasmic islet cell antibodies selected by the indirect immunofluorescence test on pancreas sections. Surprisingly, they all recognized the 64 kDa autoantigen glutamate decarboxylase. In this study we investigated which typical features of cytoplasmic islet cell antibodies are represented by these monoclonals. We show by double immunofluoresc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
13
0

Year Published

1994
1994
2005
2005

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 20 publications
2
13
0
Order By: Relevance
“…A limited analysis of nine children with newly diagnosed type 1 diabetes suggested that MICA 1-6 represent a wide range of both common and unusual epitopes (94). However, no disease-specific GAD65Ab changes in the preclinical stages of type 1 diabetes were identified using these reagents (90).…”
Section: Daa Epitopesmentioning
confidence: 99%
“…A limited analysis of nine children with newly diagnosed type 1 diabetes suggested that MICA 1-6 represent a wide range of both common and unusual epitopes (94). However, no disease-specific GAD65Ab changes in the preclinical stages of type 1 diabetes were identified using these reagents (90).…”
Section: Daa Epitopesmentioning
confidence: 99%
“…In most IDDM patients, ICAs only stain frozen and not fixed sections of human pancreas. Thus, ICA epitopes are dependent on conformation of the relevant antigen [22]. Similarly diabetes associated epitopes in the GAD6s molecule are predominantly conformational and only the sera of very few patients recognize a linear epitope in the protein [12,19].…”
mentioning
confidence: 99%
“…This suggests that amino acid residues in the middle and C-terminal regions of the protein interact to form a conformation-dependent GAD65Ab epitope that is easily destroyed by substituting glutamic acid with proline at position 517. We compared the binding of wild-type GAD65 and GAD65-E517P by GAD65 monoclonal antibodies recognising different regions of the GAD65 molecule (Group A, Table 1), including mAb144 [19], GAD6 [20] and MICA [11,21] (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…Type 1 diabetes sera primarily recognise conformational GAD65 epitopes, and GAD65Ab binding is easily lost when the target antigen is denatured, such as in ELISA and western blots or following mutagenesis [11,12,13]. The ability to identify diabetes-specific GAD65Ab that recognise conformation-dependent epitopes would enhance the value of GAD65Ab as a predictive marker.…”
mentioning
confidence: 99%
See 1 more Smart Citation